Country Partnership Framework for the Republic of Haiti for the Period FY16-FY19 - World Bank Group (World Bank, Washington, DC, 2015)
Five years into Haiti’s reconstruction following the devastating earthquake of 2010, the country is experiencing an economic and a political transition. Although many challenges brought by the earthquake remain to be fully addressed, Haiti’s focus has shifted from reconstruction to longer term development and to securing a more prosperous future for its people. This World Bank Group (WBG) Country Partnership Framework (CPF) for FY2016-2019 proposes to support Haiti’s efforts to reduce poverty and boost shared prosperity, in line with the priorities of the Government of Haiti. This CPF follows two Interim Strategy Notes (ISNs), which framed the WBG’s significant post-earthquake response over the FY2012-2015 period, financed by an exceptional allocation from the IDA 16 Crisis Response Window (US$500M equivalent). Over this period a substantially expanded WBG program supported reconstruction. However, the program was also designed to continue to help the country address its long term development challenges and capitalize on new opportunities as Haiti gradually transitioned out of the reconstruction phase. Today, a CPF aimed at long-term objectives is appropriate.